The influence of aeolian dust on the biogeochemical and physical characteristics of soils across three bioclimatic domains of the western U.S. - Callen, Jessica, author; Kelly, Eugene, advisor; Melzer, Suellen, advisor; Butters, Gregory, committee member; Magloughlin, Jerry, committee member (Colorado State University. Libraries, 2023)
This study investigates the impacts of dust generation and deposition on the biogeochemistry of soils in the western U.S., where aeolian processes are increasing due to climate change and human activities. Contemporary techniques for collecting and analyzing erosion and deposition were utilized at three locations (Moab, Niwot, CPER) to determine the amount and properties of dust present in three bioclimatic domains (Colorado Plateau, Rocky Mountains, Great Plains). The processes that contribute to the aggradation and degradation of the soil were assessed and used to determine the role of dust in the soil-forming processes at each site. These results indicate that the high amount of soil eroding at Moab (160 times more erosion than deposition) was causing a decrease in the soil volume and creating a loss of clay and plant essential nutrients within the surface horizon. For both Niwot and CPER, the soils were formerly in an aggrading phase but the measurements from soil erosion samplers at these sites indicate the contemporary system are now degrading. The chemical characteristics of deposited dust compared to the soil at Niwot suggest that the Southern Rocky Mountains are receiving dust from non-local sources, specifically Moab within the winter season. The results from CPER suggest deposition is from local dust generation. Based on these findings, it can be inferred that the impact of aeolian processes on the soils varies across bioclimatic domains.
Keywords: erosion; pedology; western U.S.; mass balance; dust; soil formation